An open-label, parallel-group, randomised controlled trial of antiseptic mouthwash versus antibiotics for oropharyngeal gonorrhoea treatment (OMEGA2) - Chow, Eric P. F. (Sci Rep, 2020)
New treatments for oropharyngeal gonorrhoea are required to address rising antimicrobial resistance. We aimed to examine the efficacy of a 14-day course of mouthwash twice daily compared to standard treatment (antibiotic) for the treatment of oropharyngeal gonorrhoea. The OMEGA2 trial was a parallel-group and open-labelled randomised controlled trial among men with untreated oropharyngeal gonorrhoea that was conducted between September 2018 and February 2020 at Melbourne Sexual Health Centre in Australia. Men were randomised to the intervention (rinsing, gargling and spraying mouthwash twice daily for 14 days) or control (standard treatment) arm and followed for 28 days. Participants in both arms were advised to abstain from sex and kissing with anyone for 14 days after enrolment. Oropharyngeal swabs were collected at baseline, Day 14 and Day 28 and tested for Neisseria gonorrhoeae by nucleic acid amplification test (NAAT) and culture. The primary outcome was the detection of oropharyngeal N. gonorrhoeae by NAAT at Day 14 after treatment. This trial was registered on the Australian and New Zealand Clinical Trials Registry (ACTRN12618001380280). This trial stopped early due to a high failure rate in the mouthwash arm. Twelve men were randomly assigned to either mouthwash (n = 6) or standard treatment (n = 6). Of the 11 men who returned at Day 14, the cure rate for oropharyngeal gonorrhoea in the mouthwash arm was 20% (95% CI 1–72%; 1/5) and in the standard treatment arm was 100% (95% CI 54–100%; 6/6). A 14-day course of mouthwash failed to cure a high proportion of oropharyngeal gonorrhoea cases.